Candidate gene regions and genetic heterogeneity in gluten sensitivity. Issue 5 (1st May 2001) - Holopainen, P; Mustalahti, K; Uimari, P; Collin, P; Mäki, M; Partanen, J
Abstract : BACKGROUND: Gluten sensitivity is a common multifactorial disorder, manifested in the small intestine or on the skin as typical coeliac disease or dermatitis herpetiformis, respectively. The only established genetic risk factor is HLA DQ2. AIMS: We tested genetic linkage of previously reported chromosomal loci 5q and 11q in Finnish families with gluten sensitivity. We also tested if genetic linkage to candidate loci on 5q, 11q, 2q33, and HLA DQ differed with respect to clinical manifestations or sex. SUBJECTS: We studied 102 Finnish families with affected sibpairs. For heterogeneity analysis, families were divided into subgroups according to sex and the presence of dermatitis herpetiformis, the skin manifestation of gluten sensitivity. METHODS: Non-parametric linkage between microsatellite markers and disease was tested. Linkage heterogeneity between subgroups was tested using the M test. The transmission/disequilibrium test and association analysis were performed. RESULTS: Evidence of linkage to 11q (MLS 1.37), but not to 5q, was found in the entire dataset of 102 families. Heterogeneity between subgroups was suggested: families with only the intestinal disease showed linkage mainly to 2q33 whereas families with dermatitis herpetiformis showed linkage to 11q and 5q, but not to 2q33. Linkage in all three non-HLA loci was strongest in families with predominantly male patients. HLA DQ2 conferred much stronger susceptibility to females than males. CONCLUSIONS: Independent evidence for the suggested genetic linkage between 11q and gluten sensitivity was obtained. The possible linkage heterogeneity suggests genetic differences between intestinal and skin manifestations, and the gender dependent effect of HLA DQ2.